Ectodermal Dysplasia: A Case Report of Aesthetic and Functional Rehabilitation - Jnana Ranjan Swain1 , Sushant Mohanty2 , Sonu Acharya3 , Bismay Singh4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
During the development of embryo ectodermal dysplasia occurs as a consequence of disturbances of theendoderm. Clinical features include hypotrichosis and palmoplantar hyperkeratosis or alopecia,a triad of naildystrophy,a partial or complete absence of primary and/or permanent dentition,and lack of sweat glands. Inthis study, the syndrome ectodermal dysplasia shows a severe case of anodontia. Since the oral rehabilitationof these cases is often difficult; particularly in pediatric patients, treatment should be administered by amultidisciplinary team involving pediatric dentistry, orthodontics, prosthodontics, and oral-maxillofacialsurgery.